HUBUNGAN KUNJUNGAN PEMERIKSAAN KEHAMILAN DENGAN KEJADIAN TANDA BAHAYA DI DESA TANJUNG MORAWA A DELI SERDANG - Surya Anita; Dewi Rismauli Bancin; Friska Sitorus (Jurnal Delima Harapan, 2022)
Abstract ANC (Antenatal Care) is a planned program in the form of observation, education, and medical treatment for pregnant women, with keeping the mother healthy during pregnancy childbirth as well as maintaining a healthy baby a safe and satisfying process of pregnancy and childbirth monitor possible pregnancy risk, planning optimal management of high-risk pregnancies and reduce perinatal maternal and fetal morbility and mortality (Fitrayeni et al., 2015). The purpose of this study was to determine the Relationship between Pregnancy Examination Visits for Hazard Signs in Tanjung Morawa Village, Deli Serdang Regency. The type of research carried out was observational-analytic. cross-sectional. From the results of the study, there was a correlation between antenatal care visits and the incidence of proven danger signs where the p-value was 0.039. Pregnant women routinely have pregnancy check-ups according to the standards of at least 4 times during pregnancy as an early detection effort For health workers to make home visits to check the mother's pregnancy as well as provide information about danger signs during pregnancy that can occur to the mother and her baby